Deletions in 14q24.1q24.3 are associated with congenital heart defects, brachydactyly, and mild intellectual disability. Issue 3 (19th December 2013) - Oehl‐Jaschkowitz, Barbara; Vanakker, Olivier M.; De Paepe, Anne; Menten, Björn; Martin, Thomas; Weber, Georg; Christmann, Alexander; Krier, Romain; Scheid, Simone; McNerlan, Susan E.; McKee, Shane; Tzschach, Andreas
<x xml:space="preserve">Abstract</x> Interstitial deletions of chromosome band 14q24.1q24.3 are apparently very rare. We report on three unrelated patients with overlapping de novo deletions of sizes 5.4, 2.8, and 2.3 Mb in this region. While some clinical problems such as intestinal malrotation, cryptorchidism, and ectopic kidney were only observed in single patients, all three patients had mild intellectual disability, congenital heart defects (truncus arteriosus, pulmonary atresia, atrial septal defect, and/or ventricular septal defect), brachydactyly, hypertelorism, broad nasal bridge, and thin upper lips. Likely haploinsufficiency of one or several of the 19 genes in the common deleted interval (ACTN1, DCAF5, EXD2, GALNTL1, ERH, SLC39A9, PLEKHD1, CCDC177, KIAA0247, LOC100289511, SRSF5, SLC10A1, SMOC1, SLC8A3, ADAM21P1, COX16, SYNJ2BP, SYNJ2BP‐COX16, ADAM21) was responsible for these manifestations, but apart from SMOC1, mutations in which cause autosomal recessive Waardenburg anophthalmia syndrome, and ACTN1, mutations in which are associated with congenital macrothrombocytopenia, no disease associations have so far been reported for the other genes. Functional studies and a systematic search for mutations or chromosome aberrations in this region will elucidate the role of individual genes in the clinical manifestations and will provide insight into the underlying biological mechanisms. © 2013 Wiley Periodicals, Inc.